PEMANFAATAN GEOGEBRA DALAM PEMBELAJARAN GRAFIK FUNGSI PADA RANAH KOMPETENSI KETERAMPILAN - Ariesta Wulandari, Diarani (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Technology development helps people to do many tasks easier, faster and efficient. In mathematics, we obtain many advantages of technology such as software or hardware as media for learning. One of media for mathematics learning is GeoGebra as the technology computer program. GeoGebra is a software which encompasses algebra, geometry, calculus and graphics function as a media to demonstrate, visualize and construct the mathematical concepts. Graphics function is one of topics in mathematics which can be learned through GeoGebra. The 2013 Curriculum has formulated three basic competencies for students which are affective, cognitive and psychomotor. GeoGebra can be used as a media for students developing their psychomotor competency in Graphics Function. GeoGebra can be an alternative to help student studying graphics function with fun, easier and meaningful.